The effects of partisan alignment on the allocation of intergovernmental transfers: differences-in-differences estimates for Spain - Albert Solé-Ollé; Pilar Sorribas-Navarro (Center for Economic Studies and ifo Institute (CESifo), 2006)
In this paper we test the hypothesis that municipalities aligned with upper-tier grantor governments (i.e., controlled by the same party) will receive more grants than those that are unaligned. We use a rich Spanish database, which provides information on grants received by nearly 900 municipalities during the period 1993-2003 from three different upper-tier governments (i.e., Central, Regional and Upper-local). Since three elections were held at each tier during this period, we have enough within-municipality variation in partisan alignment to provide differences-in-differences estimates of the effects of alignment on the amount of grants coming from each source. Moreover, the fact that a municipality may simultaneously receive grants from aligned and unaligned grantors allows us to use a tripledifferences estimator, which consists of estimating the effects of changing alignment status on the change in grants coming from the aligned grantors relative to the change in grants coming from the unaligned ones. The results suggest that partisan alignment has a sizeable positive effect on the amount of grants received by municipalities.
Keywords: C72; D72; 330